Banking Operations and Development in India: Exploring the Role of Banking Operations and Development in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India is not only the world’s largest independent democracy, but also an emerging economic giant. Without a sound and effective banking system, no country can have a healthyeconomy. Banks play a vital role in the economic development of a country. Theyaccumulate the idle savings of the people and make them available for investment. The Department of Banking Operations Development is entrusted with theresponsibility of regulation of commercial banks under the regulatory provisions contained in the B.R. Act, 1949 and RBI Act, 1934 besides enunciation of banking policies. Its functions broadly relate to prescription of regulations for compliance with various provisions of Banking Regulation Act on establishment of banks such as licensing, branch expansion, maintenance of statutory liquidity, management and operations, amalgamation, reconstruction and liquidation of banking companies and issue of guidelines on Prudential Norms relating to CapitalAdequacy, investments and loans. In order to achieve its objective, it has to maintain aflexible organizational set-up with activities in tune with the time. This paper delineates aspects of banking operations and development in india. The study also deals with the need for a regulatory body to regulate, develop and guide the numerous bank and financial institution who work in the field of banking. The paper discusses the factors and theoretical position associated with banking operation.